Determinants of food purchase practices and their contribution towards food accessibility by household from Imbali township, Pietermaritzburg, Kwa-Zulu Natal, South Africa - Malinga, Fundisiwe Feziwe (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc Food Sc)--Stellenbosch University, 2019.